E-commerce promotes trade in invasive turtles in China. Issue 3 (17th May 2021) - Liu, Sha; Newman, Chris; Buesching, Christina D.; Macdonald, David W.; Zhang, Yu; Zhang, Kai-Jie; Li, Feng; Zhou, Zhao-Min
Abstract: Freshwater habitats in China are potentially suitable for invasive alien turtle species and, consequently, raising turtles in aquaculture facilities and the trade in turtles this supplies pose risks to habitats and native wetland communities when exotic turtles escape or are released deliberately. Online trade (e-commerce) is making an increasing contribution to turtle sales in China, seemingly driving demand and thus potentially exacerbating the risk of release. We document the scale and spatial pattern of online sales of non-native turtles over 90 days on China's Taobao.com e-commerce site. The majority of sales were in the ecologically sensitive middle and lower Yangtze river basin (82.35% of > 840, 000 slider turtles Trachemys scripta elegans, and 68.26% of > 100, 000 snapping turtles, Chelydridae spp.). These species are native to the Americas. Concurrently, over 2008–2018, we found 104 mentions of feral turtle issues listed on Baidu News where, among the 53 prefectures mentioned, issues with invasive turtle populations also focused predominantly in the middle and lower Yangtze river basin. Although circumstantial, this association suggests that the substantial online sale of alien turtles could be having detrimental effects in China's Yangtze river basin. It is important to safeguard these wetland habitats, which are of global importance, by improving policies for detecting and regulating invasive alien turtle issues and by warning consumers about the ecological hazard of their purchases.